2019
DOI: 10.1007/s40071-019-00234-2
|View full text |Cite
|
Sign up to set email alerts
|

Effect of arsenic (As) and lead (Pb) on glycogen content and on the activities of selected enzymes involved in carbohydrate metabolism in freshwater catfish, Heteropneustes fossilis

Abstract: Heavy metals show a wide range of effect on fishes, out of which arsenic (As) and lead (Pb) are among the leading heavy metal toxicants. These heavy metals are known to alter different biochemical parameters, including glycogen level, in different tissues of fishes. Glycogen level in fish serves as the main source of energy; hence, in this study, the acute toxicity test of As and Pb and their effect on the glycogen content and the enzymes involved therein (glycogen phosphorylase, glycogen synthase, hexokinase,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 33 publications
2
6
0
Order By: Relevance
“…Recently, Tewari et al (2019) reported a decrease in glycogen concentrations in gill, liver, kidney, and muscle at 4, 7, 15, and 30 days’ exposure to CdCl 2 . The exposure of As 2 O 3 and PbCl 2 has also been reported to disturb carbohydrate metabolism in Heteropneustes fossilis ( Tariang et al, 2019 ).…”
Section: Discussionmentioning
confidence: 99%
“…Recently, Tewari et al (2019) reported a decrease in glycogen concentrations in gill, liver, kidney, and muscle at 4, 7, 15, and 30 days’ exposure to CdCl 2 . The exposure of As 2 O 3 and PbCl 2 has also been reported to disturb carbohydrate metabolism in Heteropneustes fossilis ( Tariang et al, 2019 ).…”
Section: Discussionmentioning
confidence: 99%
“…Bhilave et al 28 also found lower levels of glucose, glycogen, and protein under the effect of chronic heavy metals exposure. Lately, in Heteropneustes fossilis the As 2 O 3 and PbCl 2 exposure lead to disturbance in the carbohydrate metabolism 29 .
Figure 2 Illustrates the ( a ) blood glucose, ( b ) serum protein, ( c ) glycogen levels in serum and liver of exposed and reference Bagarius sp.
…”
Section: Resultsmentioning
confidence: 99%
“…The dimension in the lipid content during different phases of the ovarian cycle of Mystus (M.) vittatus (Bl. ), a freshwater siluroid might be partly due to its utilization in cell repair and tissue organization with the formation of lipoprotein, which is a salient constituent of the cell membrane and cytoplasmic organelles [26][27][28][29] .…”
Section: Resultsmentioning
confidence: 99%